A Simple, Cheap and Precise Microcontroller Based DDS Function Generator - Ali Rospawan; Joni Welman Simatupang; Irwan Purnama (Journal of Electrical And Electronics Engineering, 2021)
In electronics design and troubleshooting, the function generator is an important and versatile electronic test equipment. But the prices of finished function generator sold on market is expensive and not everyone can afford it. In order to create an economic and reliable function generator, microcontroller-based DDS function generator designed. AD9833 is DDS based programmable function generator from Analog Devices, which capable to producing sine, triangular and square wave output. To make an easy to use and flexible function generator, AD9833 connected with 4x4 matrix membrane keypad and LCD 1602. The microcontroller-based DDS function generator successfully created. The waveform generated by AD9833 offers not only exceptional accuracy and stability, but also low phase noise, an excellent frequency change and sudden waveform change ability, its useful in a wide variety of testing applications.